Lattice Boltzmann simulation on the flow behaviour associated with Helmholtz cavity-backed acoustic liners - Heng, Jinliang (2022)
Noise from jet engines can be reduced by means of a Helmholtz cavity configuration. The resonance that occurs when a flow passes the neck of the Helmholtz resonator will dissipate acoustic energy. The mechanism for such dissipation is mainly due to the vortex shedding that occurs at the neck of the resonator where the vortex structures absorb acoustic energy and subsequently dissipate it through viscous effects. In this work, numerical simulations utilizing the lattice Boltzmann method are used to aid in visualizing the flow behaviour that is associated with Helmholtz cavity-backed acoustic liners. In both experiments and numerical simulations, the 1-neck cavity is found to result in an amplification of an applied acoustic source. For a 4-neck cavity, the configuration is able to achieve acoustic pressure reductions. Differences in the flow behaviour of the 1-neck and 4-neck cavities are detailed in this work. Results show that the stronger vortex shedding that occurs in the 4-neck cavity configuration could explain its increased effectiveness as a Helmholtz cavity-backed acoustic liner.